2019
DOI: 10.1108/jfbm-03-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

Succession planning and performance of family-owned small and medium enterprises in Arusha City – Tanzania

Abstract: Purpose The purpose of this paper is to examine succession planning and performance of family-owned small and medium enterprises (SMEs). Design/methodology/approach The quantitative research approach and a cross-sectional research design were employed. The probability sampling technique was used to draw 219 respondents from the sampling frame. A structured questionnaire was used for data collection. Descriptive statistics and independent samples t-tests were used for data analysis. Findings It was revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 48 publications
(61 reference statements)
1
30
0
Order By: Relevance
“…The literature has long recognized small and medium enterprises (SMEs) as fundamental to the world economy, and they play significant roles in growth, employment, and wealth creation (Roux and Bengesi 2014;Kiwia et al 2020). Most of the SMEs throughout the world are family businesses (Poza and Daugherty 2014;Hnátek 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature has long recognized small and medium enterprises (SMEs) as fundamental to the world economy, and they play significant roles in growth, employment, and wealth creation (Roux and Bengesi 2014;Kiwia et al 2020). Most of the SMEs throughout the world are family businesses (Poza and Daugherty 2014;Hnátek 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the SMEs throughout the world are family businesses (Poza and Daugherty 2014;Hnátek 2015). Combinations of family businesses and SMEs in certain areas are called family-owned SMEs (Kiwia et al 2020). Family businesses and SMEs are critical components of entrepreneurship and are responsible for many contributions to the economic development of a country.…”
Section: Introductionmentioning
confidence: 99%
“…Feltham and Barnett (2005) in their study found that 61% of family business leaders had not chosen a successor nor had a plan to choose one. One of the weaknesses of most business founders is too much attachment to their business to the extent that they do not think of the future of the business in their absence (Kiwia, Bengesi, Ndyetabula, 2019) Miller et al (2003 found that there is a direct relationship between the preparation level of possible successor and the effectiveness of succession process. The higher the preparation level of a possible successor, the higher the likelihood that he or she will take over the family business after the predecessor leaves it (Miller et al, 2003).…”
Section: Figure 3: Business Readiness For the Next Successormentioning
confidence: 99%
“…There is no one standard definition of what a family business is because of the various factors, complexities and differences within family businesses such as size, percentage of ownership, the environment it operates in and other factors. Kiwia, Bengesi, and Ndyetabula, (2019) define it as a business where family members contribute to its capital and are engaged in its management, and it is intended to be transferred to the next generation. For this paper, a family business is considered as a business whose ownership as well as control is within the founder's family members, the family members are directly involved in the business' daily activities and the plan is to transfer the business to subsequent family generations.…”
Section: Introductionmentioning
confidence: 99%
“…However, the succession process and the transfer of knowledge are still under-researched, particularly in the context of collectivist societies, such as Vietnam (Pham et al, 2019). Furthermore, there have been calls for exploratory research to add depth to the understanding of the family business succession process (Kiwia et al, 2019). This study seeks to address these gaps in the literature by examining the knowledge transfer process from founder to successor, through the eyes of the two actors, in order to understand and model the factors that influence the knowledge transfer process in the Vietnamese family business context.…”
mentioning
confidence: 99%